BIOTECHNOLOGY FOR INCREASING INULIN CONTENT IN PLANTS - Tog’ayeva Muhayyo Bafoyevna; Zaripov Ma’rufjon (Web of Journals Publishing, 2025)
Information is provided on plant species containing inulin, their morpho-physiological characteristics, distribution, composition, and plant cultivation technology.
Keywords: Jerusalem artichoke, Jerusalem artichoke (Helianthus tuberosus L.), Onion (lat. Állium cépa), Watermelon (Citrullus lanatus), Banana (especially green banana), Artichoke (cynara scolymus l.) Ginger (Zingiber officinale).